Once-Weekly Semaglutide in Adults with Overweight or Obesity - Wilding, John P.H; Batterham, Rachel L; Calanna, Salvatore; Davies, Melanie; Van Gaal, Luc F; Lingvay, Ildiko; McGowan, Barbara M; Rosenstock, Julio; Tran, Marie T.D; Wadden, Thomas A; Wharton, Sean; Yokote, Koutaro; et al. (The New England journal of medicine, 2021)
This double-blind study randomly assigned adults with obesity (or overweight and with one or more weight-related coexisting conditions) without diabetes to 68 weeks of once-weekly subcutaneous semaglutide (2.4 mg) or placebo, plus lifestyle intervention. Semaglutide therapy was associated with sustained, clinically relevant weight reduction.